Experimental and numerical evaluation of piston metallic damper (PMD). (March 2019) - Jarrah, Majid; Khezrzadeh, Hamed; Mofid, Massood; Jafari, Khashayar
Abstract: In this paper, a metallic yielding damper, called piston metallic damper (PMD) is introduced for the first time. The PMD is comprised of a set of parallel hollow circular plates that interconnect inner shaft of the PMD to its outer pipe. Experiments and numerical models are used to examine its applicability as a seismic energy dissipating device. In this novel damper seismic input energy will be dissipated through flexural yielding of circular steel plates when system experiences small to medium displacements. At large displacements, tensile behavior will dominate and causes significant increase in stiffness of the system. In experimental program, different specimens were tested and the hysteretic behavior was recorded. These experiments indicate that the PMD is able to dissipate significant amount of seismic input energy with a stable hysteretic behavior, and endure code requirements for low-cycle, large-displacement fatigue. To check effect of different PMD parts on its overall behavior, at first hysteresis behavior of specimens is verified against nonlinear finite element (FE) models and it is shown that there is complete agreement between the nonlinear FE models and the test data. Afterwards, nonlinear FE model was used to conduct a parametric study on the effect of components geometry on the apparent mechanical properties of the PMD. This parametric study together with classical theory of plates yielded to the explicit formulas for the effective stiffness and yield load of the PMD. Highlights: The development of a novel passive metallic damper, called piston metallic damper (PMD) is demonstrated. This inexpensive damper can be easily fabricated and installed. Experiments and FE models indicate that PMD exhibits stable hysteretic behavior and meet code requirements for low-cycle fatigue. The PMD will enhance the structural performance by adding energy dissipation and stiffness at large lateral displacements. A parametric study is conducted on the PMD using the FE models.